Tobacco Farmer’s Willingness to Pay for Green Tobacco Sickness Risk Mitigation - Saptutyningsih, Endah; Sujud, Arifatus (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2020)
Tobacco farmers are at risk for disease due to work directly related to pesticide exposure and the absorption of wet leaf tobacco nicotine that is Green Tobacco Sickness (GTS). This study aimed to determine the value of Willingness to Pay (WTP) of tobacco farmers in the Jember Regency for health insurance because they are at risk of exposure to GTS disease. The method used in this research is a contingent valuation method (CVM). The sample of 394 respondents have interviewed. By binary logistic regression, it is showed that 64% of respondents are willing to pay health insurance, income, education level, and green tobacco sickness significantly influence the WTP, while age variable, family, and periods of work has no effect on WTP. The results of this study are expected to provide input to policy makers in the framework of providing health insurance for tobacco farmers of many regions in Indonesia.